Variação morfológica dos esqueletos de Montastraea cavernosa (Linnaeus, 1767) e Favia gravida Vernill, 1868 (Cnidaria, Scleractinia) - Amaral, Fernanda Maria Duarte do (1991)
Morphological variability is a widespread but poorly understood characteristic of many colonial animals. Skeletal variations of Montastraea cavernosa from Brazil, Abrolhos (BA), Tamandaré (PE) and Mexico, Puerto Morelos (Q.ROO) and variations of Favia gravida from Brazil, Abrolhos, Tamandaré and Santa Cruz (ES) were analyzed. At the Abrolhos reefs, samples of M. cavernosa were collected from three depths: O- 5 m, 10-15 m and 15-20 m. At the other localities, the specimens were collected at a depth of 0-5 m. Samples of F. gravida were collected at this same depth. A total of fourteen measurements were made in ten corallites on each sample. The most variable characters of M. cavernosa were: the heigth of outer columella and of theca, the diameter of corallite, and the thickness of first cycle septa. ln F. gravida: length and width of meander and the number of septa per cm. The characters of M. cavernosa, which were weighed most heavily on the first canonical variate, consist of: diameter of coralllte and the height of outer columella. ln F. gravida: number of septa per cm and of center per 9 cm², Variability of the studied characters decreased from the intrapopulational to the interpopulational level, and was always significant. The geographic vartatton was remarkable, matnly between the populations from Brazil and Mexico. Canonical analyses showed that the depth of 0-5 m was completely separated from the others which overlapped slightly. The studied species were characterized by variation according to the environmental cond1t1ons and polymorphtsm wlthln and between colantes of each population.